Coping Strategy, Life Style and Health Status During Phase 3 of Indian National Lockdown for COVID-19 Pandemic—A Pan-India Survey - Nagarathna, Raghuram; Sharma, Manjunath N. K.; Ilavarasu, Judu; Kulkarni, Ravi; Anand, Akshay; Majumdar, Vijaya; Singh, Amit; Ram, Jagat; Rain, Manjari; Nagendra, Hongasandra R. (Frontiers in Public Health, 2022)
The implementation of timely COVID-19 pan-India lockdown posed challenges to the lifestyle. We looked at the impact of lifestyle on health status during the lockdown in India. A self-rated scale, COVID Health Assessment Scale (CHAS) was circulated to evaluate the physical health or endurance, mental health i.e. anxiety and stress, and coping ability of the individuals under lockdown. This is a pan-India cross-sectional survey study. CHAS was designed by 11 experts in 3 Delphi rounds (CVR=0.85) and was circulated through various social media platforms, from 9th May to 31st May 2020, across India by snowball circulation method. CHAS forms of 23,760 respondents were downloaded from the Google forms. Logistic regression using R software was used to compare vulnerable (>60 years and with chronic diseases) with non-vulnerable groups. There were 23,317 viable respondents. Majority of respondents included males (58•8%). Graduates/Postgraduates (72•5%), employed (33•0%), businessmen (6•0%), and professionals (9•7%). The vulnerable group had significantly (OR 1.31, p<0.001) higher representation of overweight individuals as compared to non-vulnerable group. Regular use of tobacco (OR 1•62, p=0.006) and other addictive substances (OR 1•80, p=0.039) showed increased vulnerability. Respondents who consume junk food (OR 2•19, p<0.001) and frequently snack snacking (OR 1•16, p<0.001) were more likely to be vulnerable. Respondents involved in fitness training (OR 0•57, p<0.001) or did physical works other than exercise, yoga, walk or household activity (OR 0•88, p=0.004) before lockdown were less likely to be vulnerable. Majority had a very good lifestyle, 94•4% never smoked or used tobacco, 92•1% were non-alcoholic, 97•5% never used addictive substances, 84•7% had good eating habits, 75•4% were vegetarians, 82•8% had ‘good’ sleep, 71•7% did physical activities. Only 24•7% reported ‘poor’ coping ability. Depression with somewhat low feeling were more likely to be vulnerable (OR 1.26, p<0.001). A healthy lifestyle that includes healthy eating, proper sleep, physical activeness and non-addictive habits supports better coping ability with lesser psychological distress among Indian population during lockdown.